Climate-sensitive decisions and use of climate information: Insights from selected La Trinidad and Atok, Benguet agricultural producers - Celia M. Reyes; Sonny N. Domingo; Adrian D. Agbon; Ma. Divina C. Olaguera (Philippine Institute for Development Studies (PIDS), 2017)
Valuing climate information is now an important discourse in mainstream economic thinking with the development of the von Neumann-Morgenstern utility hypothesis and of the refinement of decision theory under uncertainty. This discourse is important in valuing weather information and climate-related decision support, particularly among agricultural stakeholders. The need to understand better the use and value of climate information and climate-sensitive decisions among smallholder farmers in selected farmers in Atok and La Trinidad Benguet, Philippines is the aim of this paper. Measures implemented to mitigate the effects La Nina and El Nino include changing the timing of planting and crop shifting and changing the location of crops. Farmers rely to indigenous knowledge when it comes to frost forecasting. On the average, 300 truckers from the trading post transport commodities outside the province on a daily basis. But during typhoons, many traders prefer to delay their deliveries. Farmers shared that weather/climate information is a major factor taken into consideration in their planning and crop decision making. Climate date for the rainy and or dry season was considered as the most important information they need. Given the unique microclimatic condition of the province, farmers need a localized forecast from PAGASA.
Keywords: 330; climate information; climate sensitive decisions; Benguet